From policy to practice: Inclusion and the education of the deaf child in Kenya - Mweri, Jefwa (2022)
This paper examines and analyses the challenges that inclusive educati on poses for children who are deaf and school going. Some of the chall enges discussed following Antia and Levine (2001), include but are not limited to: Linguistic diversity, procedural differences and language proficiency. We argue in this paper that as far as inclusion is conce rned, the school is just a “place” and one of the circumstances where inclusion can be practiced. However, there are also other experiences such as: the home, family, childcare and other socializing cases that cannot be precluded because of their importance. We further argue that to some extent, students who are deaf may still require a special edu cation environment especially, as Rosenqvist & Gustavsson (1993) asser t, it is important to maintain some concepts of difference in humans s ince in one way or another it may reinforce a person’s sense of identi ty, peculiarity or proficiencies. The lack of recognition of differenc es, most of the time in an inclusive setup pose numerous challenges. I n this paper we strongly advocate for the bi-bi approach (bilingual- b icultural approach), but we also believe that there is need to relook, rethink and evaluate inclusion policies in a flexible way, taking cog nizance of the distinction between the “general class or school for al l model” and the “special school model” so as to show that there is a place for special schools, and special units within schools. Research must be conducted to develop inclusive education policies that recogni ze the importance of having a range of schooling options for students with disabilities and in particular students who are deaf.